MIXED CODE GREETING CEREMONY INSTRUCTOR AT MUHAMMADIYAH VOCATIONAL AND SENIOR HIGH SCHOOLS IN PAGARALAM - Sari, Intan Purnama; Pebrianti, Ike Tri; Nopriani, Henny (Jurnal Visipena, 2025)
This research discusses the phenomenon of code mixing in the Speech of the Ceremony Supervisor at Muhammadiyah Pagaralam Vocational Schools and High Schools. Code mixing is the combination of using two or more languages in one utterance that is not always based on the need for communication, but rather as a speaker's choice in a particular context. This study aims to describe the types of code mixing used, namely inward code mixing (regional languages), outward code mixing (foreign languages), and mixed code mixing (a combination of regional languages and foreign languages). The data for this research was obtained through recordings of the ceremony supervisor's speech which took place routinely every Monday for four months at Muhammadiyah Pagaralam Vocational Schools and High Schools. The research method used is qualitative with data collection techniques of recording, observing, and noting. Data analysis is carried out by grouping, analyzing, and describing the types of code mixing that appear in the speeches. The results of this study show that The use of code-mixing in the remarks of the ceremony supervisor is influenced by cultural factors, the background of the supervisor, social interactions, and communication goals. Code-mixing serves to clarify meaning, create a friendly atmosphere, and reflect the cultural diversity and social identities of the ceremony participants. This research contributes theoretical insights to sociolinguistic studies and practical applications for teaching Indonesian language, as well as the preservation of regional languages in educational settings. Keywords: code-mixing, ceremony supervisor remarks, Muhammadiyah Vocational School Pagaralam, Muhammadiyah High School Pagaralam, sociolinguistics